Subject Experiments with a Learning Support System for Grover's Algorithm - Yasunaga, Hayato; Sasakura, Mariko; Monden, Akito (Proceedings / International Conference on Information Visualisation, 2023)
An appropriate quantum algorithm is needed for each problem to achieve the full performance of a quantum computer. It is necessary to understand the principles of quantum computation to implement quantum algorithms. Quantum computation simulators can assist in understanding the principles and behavior of quantum computation. Combining this with explanations of quantum algorithms using visualization techniques and interactions can further aid learning. In this study, to support the understanding of quantum computation, a difficult concept for beginners, we develop an interactive system in which diagrams and graphs are added to a quantum computation simulator to support the explanation and understanding of qubits and quantum algorithms. To verify the effectiveness of the interaction in supporting learning, a subject experiment is conducted to compare the amount of knowledge understood by a group of novice quantum computer students who learned using the developed system with a group who learned using paper-based materials.